Human Moral Responsibility in QS. Al-Isra' Verse 36: Ethical Interpretation in the Era of Artificial Intelligence - Rabbani, Jundyah Zahrah (Universitas Muhammadiyah Surakarta, 2025)
This article examines QS. Al-Isra':36 in the perspective of epistemic ethics and moral responsibility, as well as its relevance in responding to contemporary Artificial Intelligence (AI) ethical challenges. This verse emphasizes the prohibition of following something without a valid basis of knowledge and places hearing, sight, and heart as human epistemic devices that will be held accountable. In the Islamic tradition, knowledge is not understood as a neutral entity, but rather as a mandate that contains moral and religious implications. Through a thematic interpretation approach and normative ethical analysis, this article integrates classical and contemporary interpretations with global AI ethical discourse, particularly the concepts of responsibility gap, human accountability, and algorithm-based disinformation problems. The results of the study show that the ethical crisis in the use of AI is not just a technical issue, but an epistemic and moral crisis of humans in receiving, producing, and disseminating information. QS. Al-Isra':36 affirms that ethical responsibility cannot be transferred to technological systems, because AI lacks moral awareness and intention. Therefore, this verse can be positioned as the normative foundation of Qur'anic ethics in building an AI ethical framework that emphasizes human accountability, ethical supervision, and the formation of responsible epistemic character in the digital age.